Profil Berpikir Kritis Mahasiswa Tipe Phlegmatis dalam Pemecahan Masalah Biologi - Ali Sadikin; Kamid Kamid; Bambang Hariyadi (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2013)
The purpose of this reseach is to derseribe the phlegmatics types of students’ critical thinking in biology problem solving. The descrieptive qualitative is applied in this research. Data collecting process is done by doing interview which is based on question sheets of biology. The subjects of the phlegmatics type of students. According to Polya, critical thinking process in problem solving steps and in thinking process characteristic that consists of step (1) the identification of problem, (2) exploring interpretation and connection, (3) priorirating alternatives, (4) strategies used to resolve the problems. The research result shows that phlegmatics types of students are likely to possess critical talents. They are able to solve the problem in critical ways. Critical thinking process is seen in every step except in recheck step. They directly use planning in problem solving.